2021
DOI: 10.3390/nu13082700
|View full text |Cite
|
Sign up to set email alerts
|

Jujube Powder Enhances Cyclophosphamide Efficiency against Murine Colon Cancer by Enriching CD8+ T Cells While Inhibiting Eosinophilia

Abstract: Cyclophosphamide (CTX) is widely applied in cancer treatment. However, the outcome is often compromised by lymphopenia, myelosuppression, and gut dysbiosis. Here, we used jujube powder to enhance CTX efficiency through nurturing gut microbiota in order to facilitate favorable metabolisms. It was observed that the oral administration of jujube powder enriched CD8+ T cells in mouse MC38 colon tumor microenvironment and increased the diversity of gut microbiota and the abundance of Bifidobacteriales, which is hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…According to the modern pharmacological research findings, the amount of T lymphocytes and ratio of CD4 + /CD8 + can reflect the body's immune function status and the severity of a disease (Ynga‐Durand et al, 2021 ; Zhuang et al, 2021 ). CD3 + T cell is the general term for all mature T lymphocytes, and reflects the strength of cellular immunity directly (Guo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the modern pharmacological research findings, the amount of T lymphocytes and ratio of CD4 + /CD8 + can reflect the body's immune function status and the severity of a disease (Ynga‐Durand et al, 2021 ; Zhuang et al, 2021 ). CD3 + T cell is the general term for all mature T lymphocytes, and reflects the strength of cellular immunity directly (Guo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides and triterpenoids are potential antitumor ingredients, and the action mechanisms include the induction of apoptosis, cell cycle arrest, mitochondrial dysfunction, the reduction of inflammation, and the regulation of the intestinal microbiota. In the mice colon cancer model, dietary jujube improved the anticancer efficiency of cyclophosphamide by optimizing the intestinal microflora [45], and it reduced the number of tumors by inhibiting the activation of inflammatory signals [46]. In cell experiments, jujube polysaccharides induced G0/G1 or G2/M cycle arrest and apoptosis in colon cancer Lovo and SW620 cells, and they inhibited cancer cell proliferation [6,47].…”
Section: Auxiliary Anticancer Activitymentioning
confidence: 99%
“…They can therefore be used as an alternative to dietary interventions in CRC, especially in people who consume excessive amounts of meat products. Besides, Zhuang et al (2021) observed in their experiments that CD8 + T cells were enriched in the intestinal microenvironment of mice with CRC treated orally with jujube powder, which increased the diversity of the intestinal microflora and the abundance of bifidobacteria and thus contributed to the production of butyric acid, which could inhibit tumor growth, in cecal contents. Moreover, the use of jujube powder to enrich the intestinal flora can improve the efficacy of chemotherapy for CRC, such as cyclophosphamide.…”
Section: Reducing Intake Of Inflammatory Foodsmentioning
confidence: 99%